The Importance of Measuring Mechanical Features of Red Blood Cells in their Natural Environment - Baier, Dina; Windberger, Ursula (Current Topics on Chemistry and Biochemistry Vol. 3, 2022)
Apart from human red blood cells (RBCs), which are a common model in single cell force spectroscopy (SCFS), little is known about the parameters apparent Young's modulus (Ea) or adhesion of animal RBCs with distinct cellular characteristics. To fill this knowledge gap, we examined RBCs from chicken, horses, camels, and human fetuses, comparing the results to data from human adults. The found species-specific values can serve as a repository for further research. The first study objective was to investigate the biomechanical characteristics of certain animal RBCs used as representative models for distinct phenotypical features within one comparative approach. The second study objective was to obtain these properties under largely physiological conditions (at body temperature in autologous plasma) and to compare the outcomes with values obtained at simplified conditions (at 25°C in aqueous NaCl solution). We were interested in whether the trend by which biomechanical properties change is similar for all of our investigated RBC phenotypes or if distinct, species-specific conclusions have to be drawn. Results: Regardless of the suspension medium, Ea decreased with increasing temperature in all RBC types. Adhesion increased with higher temperatures in mammalian RBCs and scaled with reported membrane sialic acid contents. Adhesion decreased with increasing temperature only in chicken, which we attribute to a lower AE-1 concentration allowing for larger membrane undulations. At each test temperature, Ea was lower in plasma, and adhesion was completely eliminated, indicating functional cell enlargement via plasma component adsorption on the RBC surface. This elastic (solid-like) surface layer not only increased RBC size by hundreds of nanometers, but it also influenced RBC interaction with the flowing plasma. The importance of the surface layer for horse RBCs is discussed. We also found that the shear-thinning propensity of bulk blood samples in shear flow is more influenced by the shape, than by the Ea of RBCs. The study establishes the existence of an RBC surface layer and examines the significant differences between probing RBCs in physiological settings and testing cells in basic buffer.